2023
DOI: 10.1159/000529822
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Characteristics and Outcomes of Immunoglobulin A Nephropathy with Different Types of Dyslipidemia: A Retrospective Single-Center Study

Abstract: <b><i>Introduction:</i></b> Immunoglobulin A nephropathy (IgAN) is one of the most common glomerulonephritic diseases in the world. Several lines of evidence have suggested that dyslipidemia is related to the disease progression and prognosis of IgAN. However, the study is scarce on the clinicopathological characteristics and outcomes of IgAN with dyslipidemia. <b><i>Methods:</i></b> This study retrospectively analyzed 234 patients with biopsy-proven idiopathic I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Inappropriate lipid levels are correlated with a high cardiovascular risk and directly predispose patients to CKD development [37]. Hypertriglyceridemia is also significantly related to a worse prognosis of immunoglobulin A (IgA) nephropathy, commonly leading to CKD [38]. Thus, lipid abnormality management in patients with kidney damage seems vital, not only in terms of cardiovascular prevention and mortality risk reduction, but especially as a way to stabilize kidney function and to delay the need for kidney replacement therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Inappropriate lipid levels are correlated with a high cardiovascular risk and directly predispose patients to CKD development [37]. Hypertriglyceridemia is also significantly related to a worse prognosis of immunoglobulin A (IgA) nephropathy, commonly leading to CKD [38]. Thus, lipid abnormality management in patients with kidney damage seems vital, not only in terms of cardiovascular prevention and mortality risk reduction, but especially as a way to stabilize kidney function and to delay the need for kidney replacement therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated lipid levels have been reported as an independent risk factor for progression of IgAN [ 23 ]. A recent study showed that IgAN patients with dyslipidemia had a worse prognosis than those in the non-dyslipidemia group [ 24 ]. Furthermore, imaging mass spectrometry analysis revealed an altered lipid distribution pattern in the tubular areas of hyper-IgA mouse kidneys [ 25 ].…”
Section: Discussionmentioning
confidence: 99%